Money lies and extramarital ties: Predicting separate and joint occurrences of financial deception and extramarital infidelity - Dew, Jeffrey P.; Saxey, Matthew T.; Mettmann, Alison (Frontiers in Psychology, 2022)
Using social exchange theory, and a national sample of individuals, we examined predictors of the joint and separate occurrences of marital financial deception (MFD, i.e., lying to one’s spouse about the cost of an item) and extramarital infidelity (EMI). We examined how different predictors were associated with membership in three different groups (MFD with no EMI, EMI with no MFD, and both MFD and EMI) relative to the group of participants who reported neither behaviors. A multinomial logistic analysis revealed that relationship satisfaction was associated with a lower likelihood of being in the MFD-only group, moral commitment was negatively associated with membership in both EMI groups, and personal dedication commitment was negatively associated with membership in both MFD groups. Flirting with someone other than one’s spouse was positively associated with being in all three groups relative to the omitted group. The personal importance of religion was not associated with group membership.